PENERAPAN APLIKASI PEMESANAN MAKANAN PADA KING’S KITCHEN & BAR - Tony Darmanto; Kartono Kartono; Tuagus Tuagus (INTEKSIS, 2021)
Information  about  the  King's Kitchen & Bar canteen is still less known to the public, especially those who often use internet access and people who want to order catering online. Ordering information system that is still manual so that to get the information the public must come directly to the King's canteen, Kitchen & Bar. By utilizing the internet technology, information in the King's Kitchen & Bar canteen is easily obtained and can also make it easier for buyers to make catering orders. Based on the results of the analysis in this study the author uses the prototype method aims to provide an idea / idea to the user about the application to be made, while the United Modeling Language (UML) is used for the operating grooves of the application made. While MySQL as a database server, Adobe Dreamweaver for PHP applications.This research resulted in the application of King’s Catering in the Web-based King’s Kitchen & Bar canteen. This application has features for ordering food menus, managing food menus, managing payment data, Customer managing Customer Profile data, and Admin managing Admin Profile data. These features are expected to help facilitate the process of ordering food to run smoothly. With this catering booking application, it can make it easy for buyers to order food, then it can facilitate sellers to promote food menus and improve service at the King’s Kitchen & Bar canteen. The conclusion obtained is that the application was designed to make it easy to order the food menu desired by the Customer, so as to benefit both parties, namely the Customer and the entrepreneur. The suggestions given are to develop further using other more modern Prototype methods that are simpler, faster to order food, and easier to use to order food. Keywords: Application, Prototype, Ordering Food, Cafeteria